Cultural Conflict and Merger Failure: An Experimental Approach - Weber, Roberto A.; Camerer, Colin F. (Management Science, 2003)
We use laboratory experiments to explore merger failure due to conflicting organizational cultures. We introduce a laboratory paradigm for studying organizational culture that captures several key elements of the phenomenon. In our experiments, we allow subjects in “firms” to develop a culture, and then merge two firms. As expected, performance decreases following the merging of two laboratory firms. In addition, subjects overestimate the performance of the merged firm and attribute the decrease in performance to members of the other firm rather than to situational difficulties created by conflicting culture.